Poverty and Consumption: A study on consumer behavior in poverty (Research, Society and Development, 2019)
Poverty indicates a state of deprivation and deprivation experienced by people and families that compromises the resources necessary for a dignified life. Children who live in a context of poverty are subject to material consumption restrictions and live in families where consumption is the basic necessities of survival. Against the background, the objective of this research is to characterize the consumption behavior of people living in poverty. In the theoretical discussion, we deal with aspects related to poverty, the consumption culture of the poor and the behavior of people living in poverty. Research has identified that poor people have aspects of consumption and deprivation that shape their behavior and their life in society. The deprivations experienced are related to health, education, housing and food. As a result of the deprivation of consumption, these people suffer emotional and social implications. As a way of coping with deprivations, they play emotional and behavioral coping strategies.